Pengaruh Penerapan Rubrik Dalam Proses Penilaian Jawaban Siswa Pada Mata Pelajaran Matematika Di Sekolah Menengah Pertama Sekabupaten Kendal - Abida, Anis Shihafiyatal; , Idris Harta, M.A., Ph.D (2015)
This study is aimed to determine whether there is or not effect of applying rubric in the assessment process to obtain more objective score on the outcome of mathematic learning at junior high school in kendal district. This research used experimental research with static group comparison approach.. The research was conducted in Mathematic Teacher Organization (MGMP) of junior high school with the math teachers in Kendal as the research subject. Determining the subject of research conducted by random sampling technique in which each math teacher was considered to have the same perceived characteristic. Data collection technique use the test method. It is used to obtain data from class VIII student of SMP N 3 Cepiring. The data was the result of the assessment process undertaken by teachers within the scope of the sample. The data were analyzed using quantitative analysis method using descriptive statistics and inferential. Descriptive statistics are statistics used to analyze the data by describing mean, variance and standard deviation. Statistics inferensial using t-test by taking requirement test consisting homogenity and normality test .In the analysis process of data obtained tcount < ttable is 0.946 <2.048 and strengthened by significance value of the hypothesis test (0.176) greater than 0.05 (α=5). Based on these result, it can be concluded that there was no effect of applying rubrics in the assessment process to obtain a student answers's score to be more objective on the outcomes of mathematic learning at junior high school in kendal district